Gregarious Flowering of Strobilanthes tomentosa (Nees) J.R.I Wood in North East India from Meghalaya - Naithani, H. B.; Kharbuli, P. (Indian Forester, 2016)
Strobilanthes tomentosa (syn. Aechmenthera tomentosa, A.gossypina) has a gregarious flowering cycle of 12 years. It has many flowering records from Uttarakhand Himalaya and last flowered in 2011. During its gregarious flowering in Chaudans Uttarakhand, the famous ’Kangdali festival’ starts every 12 years in the month of October after Dusshera festival. The production of honey increases during this period. In October 2015 Strobilanthes tomentosa called ’Jah Khei’and ’Lakhi’ gregariously flowered at Meghalaya. This is its first gregarious flowering record from Northeast India.